A functionalized MXene modification method, a diaphragm preparation method and application
By grafting functional groups on the surface of MXene and compatible with SPEEK polymer chain segments, the problem of MXene incompatibility with SPEEK is solved, the electrochemical and mechanical properties of the flow battery separator are improved, and it is suitable for a variety of flow battery systems.
Patent Information
- Application Number
- CN202411813021.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-11
AI Technical Summary
In the prior art, MXene material is incompatible with SPEEK polymer chain segments, resulting in poor mechanical properties of the flow battery separator, and the surface of MXene material does not contain sulfonic acid groups, reducing the mobility of ions.
Through gentle diazon salt reaction, different functional groups were grafted onto the surface of MXene to prepare functionalized MXene, and it was evenly dispersed in SPEEK solution by redispersion and solvent exchange method to prepare a high-performance MXene/SPEEK separator.
It improves the electrochemical performance of the flow battery separator, enhances the ion transmission rate, improves the mechanical performance, and reduces production costs. It is suitable for a variety of flow battery systems.
Smart Images

Figure CN119286061B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of liquid flow batteries and relates to a modification method of functionalized MXene, a diaphragm preparation method and application. Background Art
[0002] Liquid flow batteries have the advantages of long cycle life, flexible design, safety and reliability, and fast response. They have very broad application prospects in the field of large-scale energy storage. At present, the main problem restricting the development of liquid flow batteries is the high cost. As one of the important components of liquid flow batteries, ion exchange membranes are the main determinant of the cost of liquid flow batteries, and their performance is closely related to battery performance. As an ideal ion exchange membrane, it needs to have the following characteristics: high proton conductivity; small ion permeation; good electrochemical stability; certain mechanical properties; low cost; easy processing; environmentally friendly, etc. The commonly used SPEEK diaphragm has the characteristics of low cost and good ion selectivity. The reason is that SPEEK has stable polymer segments and abundant sulfonic acid groups on the surface. Sulfonic acid groups provide a transfer path for carriers. However, if the number of sulfonic acid groups is too high, it will affect the mechanical strength of the SPEEK diaphragm, and if the number is too low, it will reduce the path for carrier transmission.
[0003] As an emerging two-dimensional material, MXenes are considered to be an effective strategy to improve performance in the field of flow batteries due to their unique layered structure, large specific surface area, excellent surface hydrophilicity and abundant active sites. The stability and large interlayer spacing of MXenes can effectively ensure the path of ion transmission. In addition, MXene materials have stable chemical stability and are an effective flow battery diaphragm modification material.
[0004] Although MXene has good chemical stability and a large interlayer spacing, which can provide a stable ion transmission channel, its surface does not contain sulfonic acid groups, which will reduce the mobility of ions. In addition, SPEEK diaphragms are prepared by solution casting, and the solvents commonly used are organic solvents such as DMF and DMSO. The dispersibility of MXene nanosheets in organic solvents is poor, resulting in its incompatibility with SPEEK polymer segments, which also has a great impact on the mechanical properties of the diaphragm.
[0005] Therefore, developing a method for preparing functionalized MXene and solving the compatibility problem between MXene materials and SPEEK substrates are crucial to improving the performance of flow battery separator materials. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a method for modifying functionalized MXene, which is based on a mild diazonium salt reaction and can be connected with different functional groups according to application requirements to obtain functionalized MXene covalently grafted with organic small molecules.
[0007] Another object of the present invention is to provide a method for preparing a functionalized MXene / SPEEK diaphragm, which effectively solves the technical problem that dried MXene nanosheets are difficult to redisperse.
[0008] The third object of the present invention is to provide an application of a MXene / SPEEK diaphragm in a liquid flow battery, thereby improving the electrochemical performance of the liquid flow battery diaphragm material.
[0009] The technical solution adopted by the present invention is a method for modifying functionalized MXene, comprising the following steps:
[0010] S1. Prepare MXene from MAX ceramic powder by mixed acid etching method, wherein MAX is Ti3AlC2, Ti2AlC, V2AlC or Nb2AlC;
[0011] S2. Preparation of MXene nanosheets:
[0012] The prepared MXene material is immersed in an aqueous solution of an intercalation agent with a mass fraction of 12.5%-25% for cation intercalation to obtain a cation intercalated MXene material. After ice bath ultrasonic treatment and centrifugation, the suspension is collected to obtain MXene nanosheets (single layer). If the concentration of the intercalation agent exceeds this range, the MXene material may be oxidized; if the concentration is insufficient, an effective intercalation effect may not be achieved.
[0013] S3. Add dried MXene nanosheets, amino-containing aromatic organic small molecules and diazonium salt initiator in a molar ratio of 1-1.5:7-9.5:7-9.5 in sequence, where the diazonium salt initiator is tert-butyl nitrite or isoamyl nitrite; vacuum pump 3-5 times, react for 8-12 hours at a temperature of 60-80°C, and obtain functionalized MXene covalently grafted with organic small molecules.
[0014] MXene nanosheets (single layer) have poor tolerance and cannot undergo diazonium salt reactions in an acidic environment, making it difficult to graft diazotized organic molecules. Conventional diazonium salt preparation method: in an acidic environment (hydrochloric acid, sulfuric acid), sodium nitrite is added as an initiator, followed by the addition of small organic molecules containing amino groups, and the reaction is carried out under ice bath conditions; in this process, the amino groups in the small organic molecules containing amino groups are converted into diazo groups. Due to the strong acidic environments of hydrochloric acid and sulfuric acid, MXene nanosheets will directly decompose in an acidic environment. The grafting process of the embodiment of the present invention does not require the harsh reaction conditions of an acidic environment and an ice bath, and the reaction conditions are mild, thereby ensuring the structural integrity of the MXene material during the diazonium salt reaction.
[0015] Furthermore, S1 is specifically as follows: putting one weight portion of MAX ceramic powder into a mixed acid solution of HCl and HF, the mass volume ratio of MAX ceramic powder to HF aqueous solution with a mass fraction of 10-48% is 1:10-30, and the mass volume ratio of MAX ceramic powder to HCl aqueous solution with a mass fraction of 20-38% is 1:5-20. After mixing, stirring is carried out at 50-60°C for 12-48 hours at a stirring speed of 400-1200 rpm, and then the residual solid is washed with a large amount of deionized water to PH>6, and vacuum dried to obtain MXene material. The MAX ceramic powder is derived from ordinary commercial products.
[0016] Furthermore, in S2, the intercalant is tetramethylammonium hydroxide, tetrabutylammonium hydroxide, methylammonium hydroxide (CH3NH3 + OH-) or butylammonium hydroxide (C4H9NH3 + OH - ), wherein the concentration of cations in the intercalant is 0.5-5 mol / L.
[0017] Furthermore, in S2, the cationic intercalation reaction is completed by stirring at 20-45° C. for 3-6 hours, and after the reaction is completed, the residual solid is washed with deionized water until the pH is less than 8.
[0018] Furthermore, in S2, under the protection of an inert atmosphere (nitrogen or argon) or a reducing atmosphere, the MXene material is subjected to ice bath ultrasonic treatment, the ultrasonic time is 15-60 minutes, the power is 40-50 KHz, and then centrifugal treatment is adopted, the centrifugal speed is 2000-6000 rpm, the centrifugal time is 5-25 minutes, and the suspension is collected to obtain MXene nanosheets.
[0019] Furthermore, in S3, the amino-containing aromatic organic small molecule is any one of aminobenzenesulfonic acid, aminoanthraquinone or aminobenzenecarboxylic acid.
[0020] A method for preparing a functionalized MXene / SPEEK diaphragm, using the functionalized MXene obtained by the above-mentioned functionalized MXene modification method as a raw material, comprises the following steps:
[0021] Step 1: Redispersion of functionalized MXene and solvent exchange:
[0022] Aqueous solutions of tetramethylammonium hydroxide and lithium chloride are mixed in a volume ratio of 1-1.3:5-6.5 to obtain a dispersant, and dried functionalized MXene is added for dispersion; then centrifugation is performed, and after the centrifugation is completed, the supernatant is poured out, and an organic solvent DMSO, DMF or NMP is added to the lower precipitate; the centrifugation operation is repeated 3-5 times to complete the solvent replacement;
[0023] Step 2, preparation of functionalized MXene / SPEEK composite membrane:
[0024] Dissolve the dried SPEEK in DMSO, NMP or DMF organic solvent, the organic solvent is the same as step 1; add the MXene material treated in step 1, and stir at a constant temperature of 40-80°C for 0.8-5 h; prepare a SPEEK / MXene mixed solution with a MXene mass fraction of 0.1-40%; prepare a film by solution casting, pour the SPEEK / MXene mixed solution into a glass plate, heat and dry, and cool to obtain a SPEEK / MXene substrate film.
[0025] Furthermore, in step 1, the dispersion time is 30-100 seconds.
[0026] Furthermore, in step 1, the centrifugal speed is 10000-15000 rpm, and the time is 20-60 minutes.
[0027] Application of the MXene / SPEEK membrane prepared by the above-mentioned method for preparing a functionalized MXene / SPEEK membrane in liquid flow batteries.
[0028] The beneficial effects of the present invention are:
[0029] 1. In the embodiment of the present invention, tert-butyl nitrite or isopentyl nitrite is used as a diazo initiator. The amino group of the aromatic organic small molecule containing amino group is converted into a diazo group under the initiation of the diazo initiator. The generated diazo group is very easy to form free radicals and nitrogen at room temperature. The surface of MXene contains hydroxyl functional groups. The hydrogen in the hydroxyl functional group is active hydrogen. Therefore, the site activity of the hydroxyl group is high and it is easy to react with the formed free radicals to form covalent grafting. The grafted organic molecules are more stable, ensuring that the MXene nanosheets will not be destroyed. The grafting process does not require an acidic environment and harsh reaction conditions of an ice bath. The reaction conditions are mild, ensuring the structural integrity of the MXene material during the diazo salt reaction.
[0030] 2. The functionalized MXene prepared in the embodiment of the present invention can be connected with different functional groups, such as carboxyl, carbonyl, sulfonic acid, pyridine nitrogen, etc., according to application requirements.
[0031] 3. In the embodiment of the present invention, the aqueous solution of tetramethylammonium hydroxide and lithium chloride is used as a dispersant to further redisperse the dried functionalized MXene, which effectively solves the technical problem that the dried MXene nanosheets are difficult to redisperse. Subsequently, the redispersed functionalized MXene material is dispersed in different organic solvents by a solvent exchange method, and then uniformly dispersed in a SPEEK solution, thereby preparing a high-performance and widely applicable MXene / SPEEK diaphragm.
[0032] In summary, the present invention is based on a mild diazonium salt reaction, and different organic molecules and functional groups can be grafted onto the surface of MXene nanosheets as needed to prepare organic / inorganic combined functionalized materials. On this basis, the problem that MXene nanosheets are difficult to disperse into a single-layer suspension after drying is solved, and the functionalized MXene material is evenly dispersed in the SPEEK solution to prepare a high-performance and widely applicable MXene / SPEEK diaphragm, which lays a solid foundation for the large-scale application of flow batteries. It is low-cost and environmentally friendly, and is suitable for a variety of flow battery systems, including but not limited to all-vanadium flow batteries, iron-chromium flow batteries, zinc-iron flow batteries, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 This is the X-ray diffraction (XRD) pattern of V2C-SO3H prepared in Example 1.
[0035] Figure 2 This is the infrared spectrum (FIRT) of V2C-SO3H prepared in Example 1.
[0036] Figure 3 This is the TG (thermogravimetric) graph of V2C-SO3H prepared in Example 1.
[0037] Figure 4 This is the redispersion diagram of the functionalized MXene of V2C-SO3H in Example 2.
[0038] Figure 5 This is a scanning electron microscope (SEM) image of the MXene-SO3H / SPEEK composite membrane prepared in Example 2.
[0039] Figure 6 This is a battery cycle efficiency diagram of the MXene-SO3H / SPEEK composite membrane prepared in Example 2.
[0040] Figure 7 This is a graph showing the battery capacity retention rate of the MXene-SO3H / SPEEK composite diaphragm prepared in Example 2.
[0041] Figure 8 This is the infrared spectrum (FIRT) of Ti3C2-AQ prepared in Example 3.
[0042] Figure 9a This is the original element distribution (EDS) image of Nb2C-COOH obtained in Example 6.
[0043] Figure 9b yes Figure 9a Distribution map of C elements in .
[0044] Fig.9c yes Figure 9a Distribution diagram of Nb element in MgO2O3.
[0045] Figure 9d yes Figure 9a Distribution map of O element in . DETAILED DESCRIPTION
[0046] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0047] Example 1
[0048] A method for modifying functionalized MXene comprises the following steps:
[0049] S1. Preparation of MXene by mixed acid etching method:
[0050] 1 g of V2AlC ceramic powder was weighed and placed in 50 mL of an aqueous solution with a mass fraction of 48% HF+38% HCl, wherein the volume ratio of HF to HCl was 30:20, and stirred at 60 °C for 48 h at a stirring speed of 1200 rpm, and then the residual solid was washed with deionized water until the pH was > 6 to obtain a V2C material;
[0051] S2. Preparation of MXene nanosheets:
[0052] The obtained V2C material was placed in an aqueous solution of tetramethylammonium hydroxide with a mass fraction of 25%, and ion intercalation was carried out under stirring at 35°C for 6 hours to obtain a cation intercalated V2C material; then the residual solid was washed with a large amount of deionized water until the pH was less than 8. Under the protection of an inert atmosphere (nitrogen), the V2C material was subjected to ice bath ultrasonic treatment for 60 minutes at a power of 50 KHz. After that, centrifugation was performed at a speed of 2000 rpm for 25 minutes, and the suspension was collected to obtain V2C nanosheets.
[0053] S3. Preparation of functionalized MXene:
[0054] The dried MXene material, aminobenzenesulfonic acid and tert-butyl nitrite were added into the flask in sequence with a molar ratio of 1:7:7. The mixture was vacuumed three times and reacted for 8 hours at a temperature of 80°C to obtain the MXene-SO3H material.
[0055] In Example 1, the XRD test of V2C-SO3H is as follows Figure 1 As shown in Figure 2, it is confirmed that the interlayer spacing of MXene is further increased due to the introduction of sulfonic acid groups. In addition, infrared spectroscopy tests such as Figure 2 As shown, the prepared V2C-SO3H sample has the peaks at 1107, 1145 cm -1 The presence of OSO characteristic peaks confirmed the successful grafting of sulfonic acid groups. In addition, the vibration of VOC explained the grafting site at the hydroxyl functional group on the MXene surface. Figure 3 As shown, the thermogravimetric curve of the prepared V2C-SO3H material shows the grafting amount of sulfonic acid groups on the MXene surface. The above data confirm the successful preparation of the V2C-SO3H material, that is, the surface of the single-layer MXene nanosheet can be functionalized with diazonium salt.
[0056] Example 2
[0057] A method for preparing a functionalized MXene / SPEEK diaphragm comprises the following steps:
[0058] Step 1: Redispersion and solvent exchange of MXene-SO3H:
[0059] Tetramethylammonium hydroxide and lithium chloride aqueous solutions were mixed at a volume ratio of 1:5 to obtain a dispersant, and the dried functionalized MXene material prepared in Example 1 was added for dispersion for 30 seconds to complete the redispersion of the dried functionalized MXene material; the mass fraction of the tetramethylammonium hydroxide aqueous solution was 25%, and the concentration of the lithium chloride aqueous solution was 1 M. Centrifugation was used for solvent exchange, and the redispersed functionalized MXene material was centrifuged at a centrifugal speed of 10,000 rpm for 30 minutes. After the centrifugation, the supernatant was discarded, DMSO (dimethyl sulfoxide) was added, and the above centrifugation operation was repeated 3 times to complete the solvent replacement.
[0060] Step 2, preparation of MXene-SO3H / SPEEK composite membrane: Dissolve the dried SPEEK in DMSO, add the functionalized MXene material dispersed in DMOS in step 1, and stir at 80°C for 3 hours to prepare a MXene-SO3H / SPEEK mixed solution with a MXene mass fraction of 5%. Pour the MXene-SO3H / SPEEK mixed solution into a glass plate and prepare a film by solution casting. Heat and dry, and after cooling, obtain a MXene-SO3H / SPEEK substrate membrane.
[0061] In order to disperse the V2C-SO3H material in an organic solvent, such as Figure 4 As shown in Figure 2, V2C-SO3H was redispersed, and it was found that V2C-SO3H had the best dispersion in an aqueous solution of tetramethylammonium hydroxide and lithium chloride. MXene-SO3H / SPEEK composite membrane was further prepared, as shown in Figure 2. Figure 5 As shown in the SEM image of the prepared composite membrane, MXene-SO3H is well dispersed in the SPEEK substrate without obvious agglomeration, which confirms that the MXene-SO3H dispersion has been successfully prepared. In order to explore the electrochemical properties of the MXene-SO3H / SPEEK composite membrane, at room temperature, compared with the vanadium battery equipped with SPEEK membrane, the battery equipped with SPEEK / MXene composite ion exchange membrane has smaller polarization, so under constant current charge and discharge conditions, the battery efficiency is higher. The results show that the vanadium battery equipped with SPEEK / MXene composite ion exchange membrane has higher coulombic efficiency, voltage efficiency and energy efficiency than SPEEK, as shown in Figure 6 As shown. Figure 7 As shown, the capacity of the battery equipped with the SPEEK / MXene composite ion exchange membrane at room temperature is higher than that of the battery equipped with the SPEEK membrane, and the capacity retention rate is also higher than that of the battery equipped with the SPEEK membrane, indicating that the addition of MXene improves the ion conductivity while effectively hindering the transmembrane permeation of active substances, improving the ion conductivity and ion selectivity of the diaphragm. The SPEEK / MXene composite ion exchange membrane prepared in this example has good prospects for industrial application in vanadium batteries.
[0062] The MXene-SO3H / SPEEK composite diaphragm prepared in Example 2 was applied to iron-chromium flow batteries, zinc-bromine flow batteries, sulfur-iron flow batteries, sulfur-bromine flow batteries, zinc-manganese flow batteries, and sulfur-manganese flow batteries and compared with traditional carbon felt electrodes; the comparison results are shown in Table 1. The coulombic efficiency and energy efficiency of a single flow battery assembled with a MXene-SO3H / SPEEK composite diaphragm at room temperature are higher than those of a flow battery equipped with carbon felt. Therefore, the MXene-SO3H / SPEEK composite diaphragm prepared in this example is suitable for industrial applications in iron-chromium flow batteries, zinc-bromine flow batteries, sulfur-iron flow batteries, sulfur-bromine flow batteries, zinc-manganese flow batteries, and sulfur-manganese flow batteries.
[0063]
[0064] The embodiment of the present invention uses a solvent-free diazotization method to prepare a functionalized MXene material, which effectively avoids the structural damage of the MXene material by the traditional acidic diazotization process. After the diazotization process, sulfonic acid groups are introduced on the surface of the MXene material. In addition, the functionalized MXene material is dispersed in an organic solvent by a redispersion and solvent replacement method to form a stable suspension with SPEEK, thereby preparing a functionalized MXene / SPEEK composite diaphragm. In the field of liquid flow batteries, the MXene / SPEEK composite diaphragm can significantly increase the ion migration path, thereby greatly improving the ion transfer rate, while maintaining a stable layered structure, extending the cycle life of the battery, and exhibiting excellent conductivity and high catalytic activity, significantly improving the overall performance of the battery.
[0065] Example 3
[0066] A method for modifying functionalized MXene comprises the following steps:
[0067] S1. Preparation of MXene by mixed acid etching method:
[0068] Weigh 1 g of Ti3AlC2 ceramic powder and put it into 50 mL of an aqueous solution with a mass fraction of 48% HF+38% HCl, where the volume ratio of HF to HCl is 30:20, stir it at 60°C for 48 h at a stirring speed of 1200 rpm, and then wash the residual solid with deionized water until the pH is >6 to obtain Ti3C2 material;
[0069] S2. Preparation of MXene nanosheets:
[0070] The obtained Ti3C2 material was placed in an aqueous solution of tetramethylammonium hydroxide with a mass fraction of 25%, and ion intercalation was carried out under stirring at 35°C for 6 hours to obtain a cation intercalated Ti3C2 material; then the residual solid was washed with a large amount of deionized water until the pH was less than 8. Under the protection of an inert atmosphere (nitrogen), the Ti3C2 material was subjected to ice bath ultrasonic treatment for 60 minutes at a power of 50 KHz. After that, centrifugal treatment was performed at a centrifugal speed of 2000 rpm for 25 minutes, and the suspension was collected to obtain Ti3C2 nanosheets.
[0071] S3. Preparation of functionalized MXene:
[0072] The dried MXene material, aminoanthraquinone and tert-butyl nitrite were added into the flask in sequence with a molar ratio of 1:7:7. The mixture was vacuumed three times and reacted for 8 hours at a temperature of 60°C to obtain Ti3C2-AQ material.
[0073] like Figure 8As shown, the infrared spectrum image of the Ti3C2-AQ material prepared in Example 3 is at 876 cm -1 The characteristic peaks confirmed the existence of Ti-OC and the successful preparation of Ti3C2-AQ materials. Therefore, the diazonium salt is applicable to the preparation of functionalized MXene for MXene materials (V2C, Ti3C2, Nb2C) and amino-containing aromatic organic small molecules (aminoanthraquinone and aminobenzenesulfonic acid), and can be grafted onto the surface of MXene according to the specific functional groups required.
[0074] Example 4
[0075] A method for modifying functionalized MXene comprises the following steps:
[0076] S1. Preparation of MXene by mixed acid etching method:
[0077] 1 g of Ti2AlC ceramic powder was weighed and placed in 50 mL of an aqueous solution with a mass fraction of 10% HF+20% HCl, wherein the volume ratio of HF to HCl was 20:5, and stirred at 50 °C for 12 h at a stirring speed of 400 rpm, and then the residual solid was washed with deionized water until the pH was > 6 to obtain a Ti2C material;
[0078] S2. Preparation of MXene nanosheets:
[0079] The obtained Ti2C material was placed in an aqueous solution of tetrabutylammonium hydroxide with a mass fraction of 12.5%, and ion intercalation was carried out under stirring at 35°C for 3 hours to obtain a cation intercalated Ti2C material; then the residual solid was washed with a large amount of deionized water until the pH was less than 8. Under the protection of a reducing atmosphere, the Ti2C material was subjected to ice bath ultrasonic treatment for 15 minutes at a power of 40 KHz. After that, centrifugal treatment was performed at a centrifugal speed of 6000 rpm for 5 minutes, and the suspension was collected to obtain Ti2C nanosheets.
[0080] S3. Preparation of functionalized MXene:
[0081] Dried MXene nanosheets, aminobenzenecarboxylic acid and isoamyl nitrite were added into the flask in sequence with a molar ratio of 1.5:9:9. The mixture was vacuumed for 5 times and reacted for 12 hours at a temperature of 70°C to obtain MXene-COOH material.
[0082] Example 5
[0083] A method for preparing a functionalized MXene / SPEEK diaphragm comprises the following steps:
[0084] Step 1: Redispersion of MXene-COOH and solvent exchange:
[0085] Tetramethylammonium hydroxide and lithium chloride aqueous solutions were mixed at a volume ratio of 1.3:6 to obtain a dispersant, and the dried functionalized MXene material prepared in Example 4 was added for dispersion for 100 seconds to complete the redispersion of the dried functionalized MXene material; the mass fraction of the tetramethylammonium hydroxide aqueous solution was 25%, and the concentration of the lithium chloride aqueous solution was 1 M. Centrifugation was used for solvent exchange, and the redispersed functionalized MXene material was centrifuged at a speed of 15,000 rpm for 20 minutes. After the centrifugation, the supernatant was discarded, DMF (N,N-dimethylformamide) was added, and the above centrifugation operation was repeated 5 times to complete the solvent replacement.
[0086] Step 2, preparation of composite diaphragm: Dissolve dry SPEEK in DMF, add the functionalized MXene material dispersed in DMF in step 1, and stir at a constant temperature of 40°C for 5 hours to prepare a MXene-COOH / SPEEK mixed solution with a MXene mass fraction of 40%. Pour the MXene-COOH / SPEEK mixed solution into a glass plate and prepare a film by solution casting. Heat and dry, and after cooling, obtain a MXene-COOH / SPEEK substrate membrane.
[0087] Example 6
[0088] A method for modifying functionalized MXene comprises the following steps:
[0089] S1. Preparation of MXene by mixed acid etching method:
[0090] Weigh 1 g of Nb2AlC ceramic powder and put it into 50 mL of an aqueous solution with a mass fraction of 30% HF+25% HCl, where the volume ratio of HF to HCl is 10:15, stir it at 55°C for 24 h at a stirring speed of 800 rpm, and then wash the residual solid with deionized water until the pH is >6 to obtain Nb2C material;
[0091] S2. Preparation of MXene nanosheets:
[0092] The obtained Nb2C material was placed in an aqueous solution of methylammonium hydroxide with a mass fraction of 20%, and ion intercalation was carried out under stirring at 35°C for 4 hours to obtain a cation intercalated Nb2C material; then the residual solid was washed with a large amount of deionized water until the pH was less than 8. Under the protection of an inert atmosphere (argon), the Nb2C material was subjected to ice bath ultrasonic treatment for 30 minutes at a power of 45 KHz. After that, centrifugal treatment was performed at a centrifugal speed of 4000 rpm for 20 minutes, and the suspension was collected to obtain Nb2C nanosheets.
[0093] S3. Preparation of functionalized MXene:
[0094] Dried MXene nanosheets, aminobenzenecarboxylic acid and tert-butyl nitrite were added into the flask in sequence with a molar ratio of 1.2:9.5:9.5, and vacuum was drawn 4 times. The reaction was carried out for 10 hours at a temperature of 70 °C to obtain Nb2C-COOH material, such as Figures 9a-9d shown.
[0095] Example 7
[0096] A method for preparing a functionalized MXene / SPEEK diaphragm comprises the following steps:
[0097] Step 1: Redispersion of MXene-COOH and solvent exchange:
[0098] Tetramethylammonium hydroxide and lithium chloride aqueous solutions were mixed at a volume ratio of 1.2:6.5 to obtain a dispersant, and the dried functionalized MXene material prepared in Example 6 was added for dispersion for 60 seconds to complete the redispersion of the dried functionalized MXene material; the mass fraction of the tetramethylammonium hydroxide aqueous solution was 25%, and the concentration of the lithium chloride aqueous solution was 1 M. Centrifugation was used for solvent exchange, and the redispersed functionalized MXene material was centrifuged at a centrifugal speed of 12,000 rpm for 60 minutes. After the centrifugation, the supernatant was discarded, NMP (N-methylpyrrolidone) was added, and the above centrifugation operation was repeated 4 times to complete the solvent replacement.
[0099] Step 2, preparation of composite diaphragm: Dissolve dry SPEEK in NMP, add the functionalized MXene material dispersed in NMP in step 1, and stir at a constant temperature of 60°C for 0.8h; prepare a MXene-SO3H / SPEEK mixed solution with a MXene mass fraction of 0.1%. Pour the MXene-SO3H / SPEEK mixed solution into a glass plate and prepare a film by solution casting. Heat and dry, and after cooling, obtain a MXene-SO3H / SPEEK substrate membrane.
[0100] The functionalized MXene prepared in the embodiment of the present invention is grafted with organic small molecules, and MXene functionalized materials grafted with different molecules can be prepared according to different needs. The prepared MXene / SPEEK diaphragm is mainly intended to solve the problems of high diaphragm cost and general stability in liquid flow battery systems. Therefore, Example 1 selects a functionalized MXene material grafted with sulfonate (-SO3H).
[0101] After a lot of experimental research, it was found that the aqueous solution of tetramethylammonium hydroxide and lithium chloride was mixed in a volume ratio of 1-1.3:5-6.5 to disperse the stacked multilayer nanosheets after drying.+ Ions, and the affinity between this ion and MXene is good. Since the MXene interlayer is negatively charged, this ion can more easily enter the MXene interlayer, thereby expanding the interlayer spacing between the MXene nanosheets. The larger interlayer spacing means that the van der Waals force between the layers is weakened, thereby dispersing the dry MXene nanosheets into single sheets.
[0102] Comparative Example 1
[0103] A method for modifying a functionalized MXene, except for S3, the remaining steps are the same as those in Example 1;
[0104] S3: Preparation of V2C-SO3H materials from conventional diazonium salts:
[0105] Select 9M hydrochloric acid and add 10ml deionized water to prepare an acidic environment, add V2C, aminobenzenesulfonic acid and NaNO2 in a molar ratio of 1:1.5:1.5, react for 5 hours at a temperature of 2°C to obtain MXene-SO3H material.
[0106] In Comparative Example 1, after the diazonium salt reaction, the acidic environment destroyed the structure of the MXene nanosheets, resulting in material decomposition, and the functionalized MXene preparation could not be achieved.
[0107] Comparative Example 2
[0108] A method for modifying a functionalized MXene, except for S3, the remaining steps are the same as those in Example 1;
[0109] S3: Preparation of V2C-SO3H materials from conventional diazonium salts:
[0110] Select 6M hydrochloric acid and add 10ml deionized water to prepare an acidic environment, add V2C, aminobenzenesulfonic acid and NaNO2 in a molar ratio of 1:1.5:1.5, react for 5 hours at a temperature of 2°C to obtain MXene-SO3H material.
[0111] In Comparative Example 2, after the diazonium salt reaction, the acidic environment destroyed the structure of the MXene nanosheets, resulting in material decomposition, and the functionalized MXene preparation could not be achieved.
[0112] Comparative Example 3
[0113] A method for modifying a functionalized MXene, except for S3, the remaining steps are the same as those in Example 1;
[0114] S3: Preparation of V2C-SO3H materials from conventional diazonium salts:
[0115] Select 3M hydrochloric acid and add 10ml deionized water to prepare an acidic environment, add V2C, aminobenzenesulfonic acid and NaNO2 in a molar ratio of 1:1.5:1.5, react for 5 hours at a temperature of 2°C to obtain MXene-SO3H material.
[0116] In Comparative Example 3, after the diazonium salt reaction, the acidic environment destroyed the structure of the MXene nanosheets, resulting in material decomposition, and the functionalized MXene preparation could not be achieved.
[0117] Comparative Example 4
[0118] A method for modifying a functionalized MXene, except for S3, the remaining steps are the same as those in Example 1;
[0119] S3: Preparation of V2C-SO3H materials from conventional diazonium salts:
[0120] Select 1M hydrochloric acid and add 10ml deionized water to prepare an acidic environment, add V2C, aminobenzenesulfonic acid and NaNO2 in a molar ratio of 1:1.5:1.5, react for 5 hours at a temperature of 2°C to obtain MXene-SO3H material.
[0121] In Comparative Example 4, after the diazonium salt reaction, the acidic environment destroyed the structure of the MXene nanosheets, resulting in material decomposition, and the preparation of MXene functionalization could not be achieved.
[0122] Comparative Example 5
[0123] A method for modifying a functionalized MXene, except for S3, the remaining steps are the same as those in Example 1;
[0124] S3: Preparation of V2C-SO3H materials from conventional diazonium salts:
[0125] 3M sulfuric acid was selected and added to 10 ml of deionized water to prepare an acidic environment. V2C, aminobenzenesulfonic acid and NaNO2 were added in a molar ratio of 1:1.5:1.5. The reaction was carried out for 5 hours at a temperature of 2°C to obtain MXene-SO3H material.
[0126] In Comparative Example 5, after the diazonium salt reaction, the acidic environment destroyed the structure of the MXene nanosheets, resulting in material decomposition, and the functionalized MXene preparation could not be achieved.
[0127] Comparative Example 6
[0128] A method for modifying a functionalized MXene, except for S3, the remaining steps are the same as those in Example 1;
[0129] S3: Preparation of V2C-SO3H materials from conventional diazonium salts:
[0130] Select 1M sulfuric acid and add 10ml deionized water to prepare an acidic environment, add V2C, aminobenzenesulfonic acid and NaNO2 in a molar ratio of 1:1.5:1.5, react for 5 hours at a temperature of 2°C to obtain MXene-SO3H material.
[0131] In Comparative Example 6, after the diazonium salt reaction, the acidic environment destroyed the structure of the MXene nanosheets, resulting in material decomposition, and the preparation of MXene functionalization could not be achieved.
[0132] Comparative Example 7
[0133] A method for preparing a functionalized MXene / SPEEK membrane, wherein except for step 1, the remaining steps are the same as those of Example 2;
[0134] Step 1: Redispersion and solvent exchange of MXene-SO3H:
[0135] The dried MXene-SO3H material was redispersed using an aqueous solution dispersant at a mass ratio of 1:20 (mass ratio of MXene-SO3H material to aqueous solution) for 30 seconds to complete the redispersion of the functionalized MXene material.
[0136] In Comparative Example 7, the aqueous solution cannot disperse the dry MXene-SO3H material, and the MXene-SO3H / SPEEK composite membrane cannot be prepared.
[0137] Comparative Example 8
[0138] A method for preparing a functionalized MXene / SPEEK membrane, wherein except for step 1, the remaining steps are the same as those of Example 2;
[0139] Step 1: Redispersion and solvent exchange of MXene-SO3H:
[0140] The dried MXene-SO3H material was redispersed using a LiCl solution dispersant at a mass ratio of 1:20 (mass ratio of MXene-SO3H material to LiCl solution) for 30 seconds to complete the redispersion of the functionalized MXene material.
[0141] In Comparative Example 8, the LiCl solution alone cannot disperse the dry MXene-SO3H material, and the MXene-SO3H / SPEEK composite membrane cannot be prepared.
[0142] Comparative Example 9
[0143] A method for preparing a functionalized MXene / SPEEK membrane, wherein except for step 1, the remaining steps are the same as those of Example 2;
[0144] Step 1: Redispersion and solvent exchange of MXene-SO3H:
[0145] The dried MXene-SO3H material was redispersed using a DMF solution dispersant at a mass ratio of 1:20 (mass ratio of MXene-SO3H material to DMF solution) for 30 seconds to complete the redispersion of the functionalized MXene material.
[0146] In this comparative example, the DMF solution is an intercalation agent for the two-dimensional material, and it is still unable to disperse the dry MXene-SO3H material, and it is impossible to prepare the MXene-SO3H / SPEEK composite membrane.
[0147] Comparative Example 10
[0148] A method for preparing a functionalized MXene / SPEEK membrane, wherein except for step 1, the remaining steps are the same as those of Example 2;
[0149] Step 1: Redispersion and solvent exchange of MXene-SO3H:
[0150] The dried MXene-SO3H material was redispersed using a DMSO solution as a dispersant at a mass ratio of 1:20 (mass ratio of MXene-SO3H material to DMSO solution) for 30 seconds to complete the redispersion of the functionalized MXene material.
[0151] In this comparative example, DMSO solution is an intercalation agent for two-dimensional materials and still cannot disperse the dry MXene-SO3H material, and cannot prepare the MXene-SO3H / SPEEK composite membrane.
[0152] Comparative Example 11
[0153] A method for preparing a functionalized MXene / SPEEK membrane, wherein except for step 1, the remaining steps are the same as those of Example 2;
[0154] Step 1: Redispersion and solvent exchange of MXene-SO3H:
[0155] The dried MXene-SO3H material was redispersed using an acetone solution dispersant at a mass ratio of 1:20 (mass ratio of MXene-SO3H material to acetone solution) for 30 seconds to complete the redispersion of the functionalized MXene material.
[0156] In this comparative example, the acetone solution cannot disperse the dry MXene-SO3H material, and the MXene-SO3H / SPEEK composite membrane cannot be prepared.
[0157] Comparative Example 12
[0158] A method for preparing a functionalized MXene / SPEEK membrane, wherein except for step 1, the remaining steps are the same as those of Example 2;
[0159] Step 1: Redispersion and solvent exchange of MXene-SO3H:
[0160] The dried MXene-SO3H material was redispersed using NMP solution as a dispersant at a mass ratio of 1:20 (mass ratio of MXene-SO3H material to NMP solution) for 30 seconds to complete the redispersion of the functionalized MXene material.
[0161] In this comparative example, NMP solution is an intercalation agent for two-dimensional materials, and it is still unable to disperse the dry MXene-SO3H material, and it is impossible to prepare the MXene-SO3H / SPEEK composite diaphragm.
[0162] Comparative Example 13
[0163] A method for preparing a functionalized MXene / SPEEK membrane, wherein except for step 1, the remaining steps are the same as those of Example 2;
[0164] Step 1: Redispersion and solvent exchange of MXene-SO3H:
[0165] The dried MXene-SO3H material was redispersed using a tetramethylammonium hydroxide (TMAOH) solution as a dispersant. The mass ratio of the MXene-SO3H material to the TMAOH solution was 1:20. The time was 30 seconds to complete the redispersion of the functionalized MXene material.
[0166] In this comparative example, tetramethylammonium hydroxide alone cannot disperse the dry MXene-SO3H material and cannot prepare the MXene-SO3H / SPEEK composite membrane.
[0167] After the MXene nanosheets are dried, it is difficult to redisperse them into single sheets due to the strong van der Waals forces between the layers. Comparative Examples 7-12 are functionalized MXene materials dispersed and dried in different solvents, and none of them can achieve the dispersion effect. Figure 4 shown.
[0168] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.
Claims
1. A method for preparing a functionalized MXene / SPEEK membrane, characterized in that: The following steps are involved: Step 1: Aqueous solutions of tetramethylammonium hydroxide and lithium chloride are mixed in a volume ratio of 1-1.3:5-6.5 to obtain a dispersant, and dried functionalized MXene is added for dispersion; then centrifugation is performed, the supernatant is discarded, and an organic solvent DMSO, DMF or NMP is added to the lower precipitate; the centrifugation operation is repeated 3-5 times to complete the solvent replacement; Step 2, dissolving the dried SPEEK in DMSO, NMP or DMF organic solvent, the organic solvent being the same as that in step 1; adding the MXene material treated in step 1, stirring at a constant temperature of 40-80°C for 0.8-5 h; preparing a SPEEK / MXene mixed solution with a MXene mass fraction of 0.1-40%; The film is prepared by solution casting method, and the obtained film is obtained; The modification method of the functionalized MXene comprises the following steps: S1. Prepare MXene from MAX ceramic powder by mixed acid etching method, wherein MAX is Ti3AlC2, Ti2AlC, V2AlC or Nb2AlC; S2, immersing MXene in an aqueous solution of an intercalation agent having a mass fraction of 12.5%-25% to perform cationic intercalation to obtain a cationic intercalated MXene material, and subjecting the MXene material to ice bath ultrasonic treatment and centrifugal treatment, collecting the suspension to obtain MXene nanosheets; S3. Add dried MXene nanosheets, amino-containing aromatic organic small molecules and diazonium salt initiator in a molar ratio of 1-1.5:7-9.5:7-9.5 in sequence, where the diazonium salt initiator is tert-butyl nitrite or isoamyl nitrite; evacuate the mixture, react for 8-12 hours at a temperature of 60-80°C, and obtain functionalized MXene with covalently grafted organic small molecules.
2. The method for preparing a functionalized MXene / SPEEK membrane according to claim 1, characterized in that: The S1 is specifically as follows: putting one part by weight of MAX ceramic powder into a mixed acid solution of HCl and HF, the mass volume ratio of MAX ceramic powder to HF aqueous solution with a mass fraction of 10-48% is 1:10-30, and the mass volume ratio of MAX ceramic powder to HCl aqueous solution with a mass fraction of 20-38% is 1:5-20. After mixing, stirring is carried out at 50-60°C for 12-48 hours at a stirring speed of 400-1200 rpm, and then the residual solid is washed with deionized water until the pH is >6, and vacuum dried to obtain the MXene material.
3. The method for preparing a functionalized MXene / SPEEK membrane according to claim 1, characterized in that: In S2, the intercalant is any one of tetramethylammonium hydroxide, tetrabutylammonium hydroxide, methylammonium hydroxide or butylammonium hydroxide.
4. The method for preparing a functionalized MXene / SPEEK membrane according to claim 1, characterized in that: In S2, the cationic intercalation reaction is stirred at 20-45° C. for 3-6 hours, and after the reaction is completed, the residual solid is washed with deionized water until the pH is less than 8.
5. The method for preparing a functionalized MXene / SPEEK membrane according to claim 1, characterized in that: In S2, the MXene material is subjected to ice bath ultrasonic treatment under the protection of an inert atmosphere or a reducing atmosphere, the ultrasonic time is 15-60 minutes, the power is 40-50 KHz, and then centrifugal treatment is adopted, the centrifugal speed is 2000-6000 rpm, and the centrifugal time is 5-25 minutes.
6. The method for preparing a functionalized MXene / SPEEK membrane according to claim 1, characterized in that: In S3, the amino-containing aromatic organic small molecule is any one of aminobenzenesulfonic acid, aminoanthraquinone or aminobenzenecarboxylic acid.
7. The method for preparing a functionalized MXene / SPEEK membrane according to claim 1, characterized in that: In the step 1, the dispersion time is 30-100 seconds.
8. The method for preparing a functionalized MXene / SPEEK membrane according to claim 1, characterized in that: In step 1, the centrifugal speed is 10000-15000 rpm, and the time is 20-60 minutes.
9. Application of a MXene / SPEEK membrane prepared by the method for preparing a functionalized MXene / SPEEK membrane as claimed in claim 1 in a liquid flow battery.
Citation Information
Patent Citations
Method for preparing functionalized graphene through ball milling
CN107445148A
Preparation method of SPEEK / MXene composite ion exchange membrane
CN117497813A